UJI PRAKTIKALITAS PENGEMBANGAN LKPD DENGAN MENGGUNAKAN MODEL PEMBELAJARAN PROJECT BASED LEARNING PADA MATERI PENGUMPULAN DAN PENYAJIAN DATA - Ummul Khaira (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
This study aims to determine the practicality development of Project Based Learning worksheets. At the practicality stage, the LKPD with the project based learning model includes very practical criteria with an average percentage of 89.78% with details of the teacher response questionnaire 90.62% and the student response questionnaire 88.59%. Based on the results of the study, it can be concluded that the LKPD in collecting material and presenting data using the project based learning model meets very valid and very practical criteria to be used as one of the learning materials in learning mathematics, especially for fifth grade students in elementary schools. Keywords: Practicality, LKPD, Project Based Learning